1971
DOI: 10.1364/ao.10.001519
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Transmission Through a Dielectric Optical Waveguide

Abstract: Waveguide propagation of a pulse-modulated carrier wave is formulated to include distortion due to dispersion in both attentuation and phase velocity. An optimum input gaussian pulse width exists for maximum information carrying capacity. Results are applied to a numerical study of several singlemode glass optical waveguides in which mode and dielectric dispersion may total zero at some wavelength. For our low-loss (20 dB/km) guides in kilometer lengths, information rates of at least 3 x 10(10) bits/sec should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…To allow a very simple analysis of the properties of a typical AWG and also to assess those aspects of its lter performance that are important in high speed limits, an analytical form has been found that can represent the propagation of a Gaussian pulse in a dielectric 164 S. A. Shahkooh and I. H. White waveguide [7]. This uses a Fourier transform method and Taylor expansion of amplitude response and propagation constant .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To allow a very simple analysis of the properties of a typical AWG and also to assess those aspects of its lter performance that are important in high speed limits, an analytical form has been found that can represent the propagation of a Gaussian pulse in a dielectric 164 S. A. Shahkooh and I. H. White waveguide [7]. This uses a Fourier transform method and Taylor expansion of amplitude response and propagation constant .…”
Section: Introductionmentioning
confidence: 99%
“…However, a closed form is used to determine the propagation of a Gaussian pulse from a single frequency source or that of limited bandwidth [9,10]. However, apart from [7], these references assume a at amplitude response for the optical ber, including the fourth term of the expansion to investigate the effect of phase response.…”
Section: Introductionmentioning
confidence: 99%
“…In fact the ultimate low loss fiber achieved to date was a single mode fiber with a loss minimum of 0.2 dB/km at 1.55 μιη [2]. Experimental realisation of such extremely low loss single mode fibers has generated a great deal of interest to deploy single mode fibers in long-haul, high capacity systems because inherently the single mode fibers possess a very much wider bandwidth as compared to multimode fibers [3,4]. The bandwidth of a single mode fiber is limited only by the wavelength dispersion i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One is due to Gloge [4] which neglects the difference in the material dispersion characteristics of the core and the cladding by making use of the later mentioned equation (3) as outlined in the theory section. One is due to Gloge [4] which neglects the difference in the material dispersion characteristics of the core and the cladding by making use of the later mentioned equation (3) as outlined in the theory section.…”
Section: Introductionmentioning
confidence: 99%
“…Computation of the bandwidth to be expected in single-mode cladded fibres [1,2] predicts values of tens of gigahertz over tens of kilometres although experimental measurements have not yet been made. On the other hand for multimode cladded fibres dispersions corresponding to bandwidths approaching a gigahertz per kilometre have been measured [3] with a mode-locked helium/neon laser and are in agreement with theory when the lossy nature of the cladding is taken into account [4,5].…”
Section: Introductionmentioning
confidence: 99%